Clustering Analysis of Premier Research Fields - ., Terttiaavini; Zamzam, Fakhry; Ramadhan, Mustafa; K. Rosni, Azrai’ie; Setiawan Saputra, Tedy; Heryati, Agustina; ., Dhamayanti (International Journal of Engineering and Technology, 2018)
The clusterization is one of methods which utilized to grouping a dataset which has a specific characteristics value. The processed data can be numerical or non-numerical data. Non-numeric data must be transformed first into numerical data. The case study in this study was to group research from six fields of science. The research data is non-numerical data is converted into the research contributions percentage in the science field. Utilized the c-means algorithm, the data was successfully grouped into three excellent research fields. The aim of the clustering is to know how many researchers in one cluster. Dataset is processed by utilizing the c-means algorithm to generated 3 clusters, they are an expeditious technology, entrepreneur and economic creative development, social engineering and strategic area infrastructure development. The data clustering result is presented in the graphic form by utilized the studio Rapidminer application.Â Â